Influence of bovine serum albumin and fetal bovine serum supplementation during in vitro maturation on lipid and mitochondrial behaviour in oocytes and lipid accumulation in bovine embryos - Del Collado, Maite [UNESP]; Saraiva, Naiara Z.; Lopes, Flavia L. [UNESP]; Gaspar, Roberta C. [UNESP]; Padilha, Luciana C. [UNESP]; Costa, Roberta R.; Rossi, Guilherme F. [UNESP]; Vantini, Roberta [UNESP]; Garcia, Joaquim M. [UNESP] (My University, 2016)
Proper oocyte maturation is crucial for subsequent embryo development; however, oocyte mitochondrial and lipid-droplet behaviour are still poorly understood. Although excessive lipid accumulation during in vitro production (IVP) of bovine embryos has been linked with impaired cryotolerance, lipid oxidation is essential for adequate energy supply. Fetal bovine serum (FBS) and bovine serum albumin (BSA) are supplements used during IVP, containing high and low lipid content, respectively. This study aimed to understand how these supplements influence oocyte mitochondrial and lipid behaviour during in vitro maturation (IVM) in comparison to in vivo maturation, as well as their influence on development rates and embryo lipid accumulation during IVP. We demonstrate that only in vivo-matured oocytes maintained correlation between lipid content and active mitochondria. IVM media containing FBS increased total lipid content 18-fold and resulted in higher lipid accumulation in oocytes when compared with media with BSA. IVM using a lower FBS concentration combined with BSA resulted in satisfactory maturation and embryo development and also reduced lipid accumulation in blastocysts. In conclusion, IVM causes changes in mitochondrial and lipid dynamics, which may have negative effects on oocyte development rates and embryo lipid accumulation. Moreover, decreasing FBS concentrations during IVM may reduce embryo lipid accumulation without affecting production rates.
Keywords: in vitro production (IVP); lipid droplet; mitochondria; reproduction